2022
DOI: 10.5530/pj.2022.14.71
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Cytotoxic Activities of Melinjo (Gnetum gnemon L.) Seed Fractions on HeLa Cell Line an In Vitro

Abstract: Introduction: Medicinal plants have been investigated for possible anti-cancer effects. One of them is Gnetum gnemon L (melinjo). This study aims determined in vitro antioxidant activity and the cytotoxic effects of polar, semipolar and non polar melinjo seed fractions againts HeLa cell line. Methods: The melinjo seed were extracted with ethanol as a solvent. Then, the fractionation was done using liquidliquid extraction method with three different polarity solvent. Cytotoxic activity was carried out using 3-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…However, the protein extract of melinjo seeds could not inhibit the proliferation of 4T1 cancer cells. But, in the present study, Sukohar et al (2022) observed that the melinjo seed fractions exhibited antioxidant and cytotoxic activity against HeLa cell lines. That melinjo seeds have the potential as an anticancer based on testing on 3 types of fractions.…”
contrasting
confidence: 49%
“…However, the protein extract of melinjo seeds could not inhibit the proliferation of 4T1 cancer cells. But, in the present study, Sukohar et al (2022) observed that the melinjo seed fractions exhibited antioxidant and cytotoxic activity against HeLa cell lines. That melinjo seeds have the potential as an anticancer based on testing on 3 types of fractions.…”
contrasting
confidence: 49%
“…Resveratrol-induced programmed cell death is evident through G1 cell cycle arrest, increased Bax release, and activation of Caspase 3 in MCF-7 cells [52]. Resveratrol stimulates caspasedependent programmed cell death through increased oxidative stress via oxygen and nitrogen in MCF-7 cells [53,54]. Resveratrol induces autophagydependent programmed cell death in HL-60 cells through intrinsic and extrinsic programmed cell death pathways.…”
Section: Effect Of Resveratrol On Caspases 8 Andmentioning
confidence: 99%